ALAUDDIN KHILJI'S MARKET REGULATIONS AND PRICE CONTROL: A RADICAL APPROACH TO ECONOMIC STABILITY - Zumeer Ahmad Sofi (Jurnal Mahasiswa Agribisnis, 2022)
This study offers an analytical review of the economic policies enacted during Alauddin Khilji's reign in the Delhi Sultanate (1296-1316), with a focus on market regulation and price control. Drawing upon economic history, political economy, and comparative economics, it evaluates the efficacy of these policies and their impact on the socio-political landscape. The paper reveals that these policies served not only economic purposes but also strategic political ones, fostering social control and political stability. By exploring similar strategies in various historical contexts, it highlights the interconnectedness of economic measures, societal factors, and political agendas. This research provides valuable insights into the complexities of market regulation, demonstrating its significant role in the broader dynamics of governance and power. It underscores the relevance of historical economic policy analysis to contemporary policy debates.